PROBLEMS OF POLITICAL SCIENCE EDUCATION AT THE HIGHER SECONDARY LEVEL IN TRIPURA: A STUDY - Dey, Pradip (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study investigates the challenges faced in political science education at the higher secondary level in schools in Tripura. Aimed at understanding the problems that hinder effective teaching and learning of political science, the research seeks to identify specific issues faced by educators and students within this context. The key research questions focus on: (1) What are the predominant problems in political science education at the higher secondary level in Tripura? and (2) How do these problems affect students’ understanding of political concepts and their overall engagement with the subject? To address these questions, a mixed-method approach was employed, combining qualitative and quantitative data collection techniques. Surveys were distributed to students and teachers across selected schools in Tripura, complemented by in-depth interviews with educators and educational administrators. The findings reveal a range of challenges, including an outdated and irrelevant curriculum, inadequate teaching resources, a lack of training for teachers in modern pedagogical strategies, and generally low student engagement levels. These issues not only impact students’ grasp of essential political concepts but also contribute to their overall disinterest in civic education. The implications of this study underscore the need for comprehensive reforms in political science education in Tripura to enhance curricular relevance, improve teaching methodologies, and ultimately foster greater student participation and interest in politics.